Implementation Of Erp-Based Open-Source Odoo For Chicken Farm Warehouse Management System Using The Quickstart Method (Studi Case: Cv. Cindil Laras) - Kartodiwiryo, Adam Yusuf; Budiono , Avon; Puspitasari, Warih (eProceedings of Engineering, 2024)
CV. Cindil Laras is a company that engaged in parent stockchicken farming that supports the demand of parent stock chickenmeat in it’s vicinity. However the growing demand of chicken meatthat directly proportional to the growth of local population makeCV. Cindil Laras suffers from mismanagement of maintaining thewarehouse and monitoring company data because the lack of asystem that support it’s business process and also the use ofconventional way on recording data result in the stagnant of thecompany growth. Odoo is an open-source business managementsoftware suite that provides a range of applications to helporganizations manage various aspects of their operations. It'sknown for its modular approach, allowing businesses to select andcustomize the specific applications that meet their needs.QuickStart is a three-stage application development methodologythat is appropriate for use in MSMEs. Existing business processeson CV will be able to be integrated by the system created. In orderto support the warehouse management process and the company'sgrowth, Cindil Laras may effectively assist in monitoring businessdata pertaining to the goods and products inside the warehouse aswell as in managing the warehouse. Keywords— enterprise resource planning (erp), warehouse, msmes, poultry, quickstart, odoo